Three Medieval Queens - St. John, Lisa Benz. author. aut Link
XII, 254 p.
Keywords: This book is an innovative study offering the first examination of how three fourteenth-century English queens, Margaret of France, Isabella of France, and Philippa of Hainault, exercised power and authority. It frames its analysis around four major themes: gender; status; the concept of the crown; and power and authority.